Integration of Conventional and Digital Marketing as an Integrated Marketing Strategy at PT Semen Indonesia Distributor - Candra Kusuma, Muhammad Gilang; Sukaris, Sukaris (INNOVATION RESEARCH JOURNAL, 2026)
Changes in consumer behavior and increasing competition in the building materials distribution industry require companies not to rely solely on conventional marketing strategies, but also to strategically optimize digital marketing. This study aims to analyze the implementation and integration of conventional marketing and digital marketing as an integrated marketing strategy at PT Semen Indonesia Distributor, Sidayu Branch. The method used is a descriptive qualitative approach. Data were collected through direct observation of the company’s marketing activities, interviews with the marketing division and Customer Relationship Officer, and documentation studies of relevant company data and reports. Observations focused on conventional marketing activities such as store visits and store treatment. The collected data were then analyzed descriptively to illustrate the actual conditions of marketing strategy implementation and the challenges faced by the company. The findings indicate that the marketing strategy at PT Semen Indonesia Distributor, Sidayu Branch is still dominated by a conventional marketing approach. The integration of conventional and digital marketing can be further optimized to strengthen customer relationships through both personal and digital communication, enhance marketing effectiveness, expand market reach, and maintain customer loyalty sustainably.